The Relationship Between Family Roles and the Independence of Activities of Daily Living (ADL) in the Elderly: Hubungan Antara Peran Keluarga Dengan Kemandirian Activity Daily Living (ADL) Lansia - Citra Suryani; Reny Tri Febriani; Sismala Harningtyas (Poltekkes Kemenkes Malang, 2025)
The elderly represent the final stage in the human life cycle, marked by a natural aging process. This process leads to various physical, mental, spiritual, and psychosocial changes that affect the independence and health of the elderly. A decline in their independence is a critical indicator of health problems in the elderly, particularly in Activities of Daily Living (ADL), such as eating, bathing, walking, using the toilet, and dressing. The family plays a crucial role in developing, preventing, adapting to, and addressing health and independence issues in the elderly. This study employed an observational analytic design with a cross-sectional approach and an accidental sampling technique, involving 61 respondents. The research instruments included questionnaires to measure family roles and the Barthel Index. Data analysis was conducted using the chi-square correlation test with SPSS IBM version 25. The results showed that 36.10% of the elderly with good family support were in the independent ADL category, 1.6% had mild independence, and none were in the moderate category. The chi-square statistical test revealed a p-value = 0.000, indicating a significant relationship between family roles and the independence of ADL in the elderly in Sumberagung Village, Selorejo District, Blitar Regency. Family roles are one of the key factor influencing the quality of life of the elderly by maintaining their independence and improving their physical, emotional, and social well-being. Active family involvement is essential in maintaining elderly independence. Programs such as family training can be implemented to enhance the role of families in sustainably supporting elderly ADL independence.